2020
DOI: 10.1002/ange.202002977
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrosyl Iron Complex [K‐18‐crown‐6‐ether][(NO)2Fe(MePyrCO2)]: Intermediate for Capture and Reduction of Carbon Dioxide

Abstract: Continued efforts are made for the utilization of CO2 as a C1 feedstock for regeneration of valuable chemicals and fuels. Mechanistic study of molecular (electro‐/photo‐)catalysts disclosed that initial step for CO2 activation involves either nucleophilic insertion or direct reduction of CO2. In this study, nucleophilic activation of CO2 by complex [(NO)2Fe(μ‐MePyr)2Fe(NO)2]2− (2, MePyr=3‐methylpyrazolate) results in the formation of CO2‐captured complex [(NO)2Fe(MePyrCO2)]− (2‐CO2, MePyrCO2=3‐methyl‐pyrazole‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Given these results with CS 2 activation and homocoupling to C 2 S 4 2− , we probed whether the reduction of CO 2 to oxalate proceeded by a similar ligand-based pathway. Indeed, a nucleophilic attack by supporting ligands was proposed in other systems as the first step toward CO 2 reduction to oxalate, 23,56 and CO 2 adducts at BDI are known (Figure 2). However, these adducts have not exhibited further reactivity beyond reversible binding; in those cases, a lack of available reducing equivalents likely precludes reductive coupling.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Given these results with CS 2 activation and homocoupling to C 2 S 4 2− , we probed whether the reduction of CO 2 to oxalate proceeded by a similar ligand-based pathway. Indeed, a nucleophilic attack by supporting ligands was proposed in other systems as the first step toward CO 2 reduction to oxalate, 23,56 and CO 2 adducts at BDI are known (Figure 2). However, these adducts have not exhibited further reactivity beyond reversible binding; in those cases, a lack of available reducing equivalents likely precludes reductive coupling.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…20−22 Recently, Liaw et al reported that CO 2 reduction to oxalate by an iron nitrosyl complex traverses a C−N bond between a ligand N atom and CO 2 (Figure 1d). 23 Examples of reversible bond formation involving only ligands have been reported but are not in the context of catalytic transformations. For instance, various groups have reported reversible C−C bonds between the para-C of aromatic ligands (e.g., pyridine bound to iron(I) βdiketiminate or a perfluorophenylimidocobalt diketimide; Figure S1).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical catalysis by metal complexes often relies on the cooperation of the ligand, either to aid in substrate bond activation or provide redox equivalents necessary for the process ( chemical vs redox noninnocence ). In contrast to the widespread applications of redox-active ligands, reports of productive catalysis by chemically noninnocent ligands are mostly limited to the support of protons or hydrogen atoms. In particular, examples in which non-H groups are involved are rare for any ligand. …”
Section: Introductionmentioning
confidence: 99%